Effect of Physıcal Therapy on Bıochemıcal Parameters in Female Patıents wıth Gonartrosıs - Güven, Aysel; Hacı Ahmet Deveci; Mustafa Gülşen; Esra Tekinyıldız (International Journal of Computational and Experimental Science and Engineering, 2025)
This study investigated the effects of hotpack, transcutaneous electrical nerve stimulation, ultrasound and home exercise program applied around the knee on blood lipid peroxidation system and antioxidant system in female patients with gonarthrosis.The group (n=32) underwent a hotpack, transcutaneous electrical nerve stimulation, ultrasound and home exercise. Sociodemographic and clinical characteristics of patients were recorded. Kan lipit peroksidasyon seviyeleri and total oxidant levels are measured with blood samples before and after treatment (4th week). A significant, positive, moderate level relationship (p=0.00) was found between reduced glutathione level and oxidative stress index level before physical therapy in female patients with gonarthrosis, and a statistically significant, negative, moderate level relationship was found between reduced glutathione level and paraoxonase activity level before physical therapy (p=0.03).No statistically significant difference was found between the reduced glutathione level and lipid peroxidation, high density lipoprotein, triglyceride and low-density lipoprotein levels of the participants (p>0.05). This will also contribute to the scientific literature by providing a new dimension that various physical therapy meth